Probing of Ultrafast Plasmon Dynamics on Gold Bowtie Nanostructure Using Photoemission Electron Microscopy - 秦将 季博宇 郝作强 林景全 (Chinese physics letters, 2015)
We report the direct imaging of plasmon on the tips pulses and probing of ultrafast plasmon dynamics by of nano-prisms in a bowtie structure excited by 7 fs laser combining the pump-probe technology with three-photon photoemission electron microscopy. Different photoemission patterns induced by the plasmon effect are observed when the bowties are excited by s- and p-polarized femtosecond laser pulses. A series of images of the evolution of local surface plasmon modes on different tips of the bowtie are obtained by the time-resolved three-photon photoemission electron microscopy, and the result discloses that plasmon excitation is dominated by the interfer- ence of the pump and probe pulses within the first 13 fs of the delay time, and thereafter the individual plasmon starts to oscillate on its own characteristic resonant frequencies.